DETECTION OF NUCLEAR APPENDAGE IN PERIPHERAL BLOOD NEUTROPHIL LEUKOCYTES FOR SEX DETERMINATION - Than Than Htwe; Anis S; Nurul A; Syuhada AM; Zafira N; Ismail S (Asian Journal of Medicine & Health Sciences, 2019)
Background: Sex determination can be done by the detection of drumstick-shaped nuclear appendage that is present in neutrophil leukocytes from peripheral blood smear of female subjects. Objectives: This study was conducted to identify a drumstick-shaped nuclear appendage on neutrophil leucocytes from peripheral blood smear and to analyse the sensitivity, specificity, positive predictive value and negative predictive value of the test in gender determination. Materials and Methods: A total of 110 randomly selected blood smears (from 40 male and 70 female subjects) with age range from 19-22 years, were stained with Jenner-Giemsa stain. At least 100 well-stained neutrophils per slide were double-blindly studied by the observers. Results: Sixty-six out of 70 female subjects and 36 out of 40 male subjects were correctly identified. There was 4 false positive result on the male subjects and 4 false negative results on the female subjects in the detection of nuclear appendage. A 94.28% sensitivity, 90% specificity, 94.28% positive predictive value and 90% negative predictive value for the study was calculated. Conclusions: The identification and detection of nuclear appendage from neutrophil leukocyte is an easily applicable method that is useful as a screening method in sex determination. Overall, the method also has a high sensitivity, specificity and predictive values.